Sorocea guilleminiana Gaudich.: Wound healing activity, action mechanisms, and chemical characterization of the leaf infusion. (10th February 2020) - Figueiredo, Fabiana de Freitas; Cechinel Filho, Valdir; Damazo, Amilcar Sabino; Arunachalam, Karuppusamy; Colodel, Edson Moleta; Ribeiro, Marlon; Venturini, Claudio Luis; Oliveira, Darley Maria; Machado, Marco Tulio Marra; Pavan, Eduarda; Paes, Raira Luiza; Tenfen, Adrielli; et al.
Abstract: Ethnopharmacological relevance: Sorocea guilleminina Gaudich. is a tree or shrub endemic to Brazil. Its leaves are used in Brazilian folk medicine for the healing of wounds, stomach problems, inflammation and as diuretic. The present study evaluates the activity and action mechanisms of the healing properties of the aqueous extract of S. guilleminiana leaves (AESg), in experimental models in vivo and in vitro, as well as performs a phytochemical analysis of the extract. Materials and methods: The AESg was prepared by infusion: Ten g of dry leaves powder in 1 L hot water, soaked for 15 min, filtered, lyophilized, and stored at −30 °C. Phytochemical analyses were realized by colorimetry and HPLC/ESI/MS. Its' in vitro cytotoxicity was evaluated on fibroblastic N3T3 cells. The potential of the wound healing activity in vivo was evaluated using excision and incision wound rat models, by histopathology of the injured skin along with the determination of nitric oxide, cytokines (IL-1β, IL-10, and TNF-α), and antioxidant parameters (GSH, MPO and CAT). In vitro wound healing activity was also demonstrated in scratched N3T3 cells, by measuring the proliferation/migration rate. Results: The phytochemical analysis of the AESg revealed a strong presence of polar compounds, especially flavonoids (4 majoritarian), as well as terpenes and/or sterols (2 majoritarian). The AESg showed no toxicity in the N3T3 cell line (IC50  > 800 μg/mL). Topical treatment with the AESg showed an increase ( p  < 0.05) in wound contraction with 2 mg/g cream on days 5 and 9 (43.56% and 6.70% increase, respectively), and with 50 mg/g on days 7 and 9 (10.88% and 7.91%, respectively), compared to the vehicle (non-ionic neutral cream). Topical application of AESg (2 or 50 mg/g non-ionic cream) in incised wounds caused an increase in the force necessary for the rupture of the wound when compared to the vehicle group. No changes in cytokines (IL-1β, IL-10, or TNF-α) or NO accumulation was found with up to 50 mg/g AESg treatment. For antioxidant activity on the incision wound, an increase in GSH levels was denoted with the AESg use, at the lowest and highest dose (2 and 50 mg/g) by 75.86% and 61.20% respectively, when compared to the vehicle. Also, the CAT activity was accentuated by AESg at the highest dose (50 mg/g) by 85.87%. Finally, the AESg at all doses attenuated MPO activity significantly in the incision wound by 71.35%, 73.21%, 78.08%, respectively. In the scratch test on N3T3 cells, the treatment with AESg resulted also in an increase in fibroblast proliferation/migration rate, compared to the vehicle. Conclusion: AESg is not cytotoxic. The results confirm the popular use of the leaf infusion of S. guilleminiana for the treatment of cutaneous wounds, possibly by stimulating the proliferation of fibroblasts with a consequent deposition of collagen, fastening rearrangement of collagen fibers, and greater transformation into myofibroblasts, essential in the healing process. Preliminary chemical analyzes of AESg revealed the presence mainly of phenolic compounds, being salicylic acid, gallic acid, pinocembrin and isoquercitrin the majoritarian ones. Graphical abstract: Image 1